Evaluation of the cost-utility of insulin degludec vs insulin glargine in Sweden. (December 2013) - Ericsson, Å.; Pollock, R. F.; Hunt, B.; Valentine, W. J.
Abstract Objective: To evaluate the annual cost-utility of insulin degludec compared with glargine in patients with: type 1 diabetes (T1D), type 2 diabetes receiving basal-only therapy (T2D-BOT), and type 2 diabetes receiving basal-bolus therapy (T2B-BB) in Sweden. Methods: A cost-utility model was programmed in Microsoft Excel to evaluate clinical and economic outcomes. The clinical trials were designed as treat-to-target, with insulin doses adjusted in order to achieve similar glycemic control between treatments, thus long-term modeling is not meaningful. Basal and bolus insulin doses, incidence of hypoglycemic events, frequency of self-monitoring of blood glucose, and possibility for flexibility in timing of dose administration were specified for each insulin in three diabetes populations, based on data collected in Swedish patients with diabetes and a meta-analysis of clinical trials with degludec. Using these characteristics, the model estimated costs from a societal perspective and quality-adjusted life years (QALYs) in the two scenarios. Results: Use of degludec was associated with a QALY gain compared with glargine in T1D (0.31 vs 0.26 QALYs), T2D-BOT (0.76 vs 0.69 QALYs), and T2D-BB (0.56 vs 0.47 QALYs), driven by reduced incidence of hypoglycemia and possibility for flexibility around timing of dose administration. Therapy regimens containing degludec were associated with increased costs compared to glargine-based regimens, driven by the increased pharmacy cost of basal insulin, but partially offset by other cost savings. Based on estimates of cost and clinical outcomes, degludec was associated with incremental cost-effectiveness ratios of SEK 19, 766 per QALY gained, SEK 10, 082 per QALY gained, and SEK 36, 074 per QALY gained in T1D, T2-BOT, and T2-BB, respectively. Limitations: The hypoglycemic event rates in the base case analysis were derived from a questionnaire-based study that relied on patient interpretation and recall of hypoglycemic symptoms. The relative rates of hypoglycemia with degludec compared to glargine were derived from a meta-analysis of phase III trials, which may not reflect the relative rates observed in real-world clinical practice. Both of these key limitations were explored in one-way sensitivity analyses. Conclusions: Based on reduced incidence of hypoglycemia and possibility for flexibility around timing of dose administration, use of degludec is likely to be cost-effective compared to glargine from a societal perspective in T1D, T2-BOT, and T2-BB in Sweden over a 1-year time horizon.